A Profile of the Furniture Manufacturing Industry - Walcott, Susan M (Business Expert Press, 2013)
Ebook from IG Library ; The furniture industry has played an important role in the history of the United States as a bellwether for manufacturing. This sector continues to be a major manufacturing employer in the US and around the world through its utilization of a global production network. Types of furniture range from household (indoor and outdoor) to institutional, with particular growth in firms supplying medical and government-related commodities. The industry is highly responsive to economic and fashion trends, but is partitioned into high, medium and low cost segments that reveal different location-al and market responses to changes in these factors. Recent developments indicate that the post-1980's migration of furniture manufacturing to offshore, low labor cost countries has stabilized and shows signs of re-shoring in the US for high end customized technologically intensive products utilizing the remaining embedded skilled labor and locally clustered industry components. Businesses that survived the recessionary 'creative destruction' largely adopted lean manufacturing processes and took advantage of newly available, lower cost equipment and buildings to upgrade their production practices, absorbing market from former competitors. New partnerships will be traced with branches and headquarter relocations in Asia, along with cooperative supplier relationships with former U.S. and new foreign companies. Industry survivors adopted practices that could be highly instructive for other manufacturers challenged by globalization to grow stronger by increasing their adaptive capacity. Concepts illustrated in the furniture industry would be useful to a number of audiences in academic, industry and public policy markets. The proposed book provides an overview of the industry and its global production network including a brief overview of the manufacturing technologies of each sector. Assessment of new competitors in Asia and South America will illustrate opportunities and challenges in these locations. The book culminates by considering challenges, opportunities, and the future outlook of the industry in regional clusters.